2011
DOI: 10.1111/j.1439-0388.2011.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters and response to selection for a continuous trait subject to culling before testing

Abstract: The consequences of assuming a zero environmental covariance between a binary trait 'test-status' and a continuous trait on the estimates of genetic parameters by restricted maximum likelihood and Gibbs sampling and on response from genetic selection when the true environmental covariance deviates from zero were studied. Data were simulated for two traits (one that culling was based on and a continuous trait) using the following true parameters, on the underlying scale: h² = 0.4; r(A) = 0.5; r(E) = 0.5, 0.0 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…; Árnason et al . ). Ducro () showed that preselection in dressage horses resulted in a lower estimate of heritability for dressage competition and a biased estimation of breeding values.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Árnason et al . ). Ducro () showed that preselection in dressage horses resulted in a lower estimate of heritability for dressage competition and a biased estimation of breeding values.…”
Section: Introductionmentioning
confidence: 97%
“…When the cause of not participating is connected with the breeding goal (preselection), this might lead to a bias in the estimated breeding values (Klemetsdal 1994;Arnason 1999). Research has demonstrated the existence of preselection in sport horses (Bugislaus et al 2005;Albertsd ottir et al 2011;Arnason et al 2012). Ducro (2010) showed that preselection in dressage horses resulted in a lower estimate of heritability for dressage competition and a biased estimation of breeding values.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, preselection has mostly been based on correlated trait(s) that can be measured easily and cheaply early in life (e.g. [ 1 , 3 , 6 8 ]). In the genomic era, preselection is often based on genomic estimated breeding values (GEBV) of young selection candidates, and in the literature this type of preselection is called genomic or genotypic preselection (GPS; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In animal breeding programs, parents of the next generation are usually selected in multiple stages (e.g., Árnason et al., 2012; Meyer & Thompson, 1984; Xu et al., 1995), and the initial stages of this selection are referred to as preselection (e.g., Janhunen et al., 2014; Masuda et al., 2018; Patry & Ducrocq, 2011). Impact of preselection on subsequent genetic evaluations has been a subject of research for a long time in the field of animal breeding (e.g., Appel et al., 1998; Henderson, 1975; Masuda et al., 2018; Patry & Ducrocq, 2011a).…”
Section: Introductionmentioning
confidence: 99%